ESTIMATE OF DISK NOT CONTAINING ROOTS OF POLYNOMIAL FUNCTIONS - Lal, Roshan (International Journal of Research -GRANTHAALAYAH, 2022)
Let is a polynomial of degree. Also let coefficients of polynomial follow a certain pattern of decreasing or increasing in magnitude. Then we have many results for providing the regions containing all the roots of polynomial functions. Here, in this paper we prove a result that gives a disk or circular region containing no roots of function, Thereby our result finally gives annular region containing all roots of polynomial function and hence thereby improves the earlier proved .results.